Immunogenicity and Protection After Vaccination With a Modified Vaccinia Virus Ankara-Vectored Yellow Fever Vaccine in the Hamster Model - Julander, Justin G.; Testori, Marco; Cheminay, Cédric; Volkmann, Ariane (Frontiers in Immunology, 2018)
The highly efficacious live-attenuated 17D yellow fever (YF) vaccine is occasionally associated with rare life-threatening adverse events. Modified Vaccinia Ankara (MVA), a non-replicating poxvirus, has been used as a vaccine platform to safely deliver various antigens. A MVA-based YF vaccine (MVA-BN-YF) was tested with and without a non-mineral oil adjuvant in a hamster model of lethal YF disease and protective efficacy of this vaccine was compared with the 17D vaccine. The vaccine candidate MVA-BN-YF generated a protective response in hamsters infected with YFV that was comparable to protection by the live 17D vaccine. Similar levels of neutralizing antibody were observed in animals vaccinated with either vaccine alone or vaccine with adjuvant. Significant improvement in survival, weight change, and serum alanine aminotransferase (ALT) levels were observed in vaccinated hamsters when administered 42 and 14 days prior to challenge with Jimenez YF virus (YFV). Neutralizing antibodies induced by MVA-BN-YF were transferred to naïve hamsters prior to virus challenge. Passive administration of neutralizing antibody 24 hours prior to virus infection resulted in significantly improved survival and weight change. A trend towards reduced liver enzyme levels was also observed. MVA-BN-YF, therefore, represents a safe alternative to vaccination with live attenuated YF virus.